Distribuição aninhada das comunidades em lagoas de inundação : relações entre a composição de Chironomidae (Diptera) e as características ambientais. - Pinha, Gisele Daiane (2012)
The species distribution model called nestedness has been used both as an important tool for exploring patterns of distribution, as from the standpoint of environmental conservation and management practices, because if the species community in a given area displays the nested pattern, the sites with high richness will behave most of the region diversity. We analyze the Chironomidae occurrence of 29 floodplain lakes, over a year of collecting, taking for assumptions that differences in environmental requirements of taxa promote distinct patterns of distribution, resulting in a nestedness of the community where it is expected that the higher the environmental similarity between two lakes, the greater the number of species shared between them. Based on the ordering of the incidence matrix, according to decreasing species richness of taxa, we recorded a strong nestedness of the Chironomidae community. From the Mantel test we can conclude that environmental variables were important in determining the composition of taxa between the ponds. This pattern was reinforced by Canonical Correspondence Analysis, which separated the lakes sampled of Paraná River to the other. Through the analysis of environmental characteristics, it was possible to predict the taxa of Chironomidae from a particular place. From these results, we outline a conceptual model of the distribution pattern of the Chironomidae community in floodplain lakes, where a nesting will develop if there is a hierarchical relationship between (1) species - in their sensitivity to limiting factors, and (2) locations - whether or not they are able to support a particular species.